Analysis of the Influence of Technological Innovativeness on Perceived Usefulness, Perceived Ease of Use, and Perceived Playfulness and their implications for Usage Intention: An analysis of LinkAja application users - Evan Tehdi; Florentina Kurniasari T (Business and Entrepreneurial Review, 2021)
By using the TAM (Technology Acceptance Model) framework, this study aims to investigate the factors that influence the usage intention of e-wallet applications, especially LinkAja, to make payments in today's digital era. Through the data collection process carried out by surveying 100 respondents, the results found show that the technological innovativeness (IT) variable can indirectly affect usage intention through the variable perceived ease of use and perceived playfulness, besides that it was also found that the variable perceived ease of use (PEU) and perceived playfulness (PP) has a positive effect on usage intention. By investigating digital payments using e-wallets as a means of transactions, this study is expected to contribute to the development of the LinkAja application as one of the largest e-wallet companies in Indonesia, because the digital economy is one of the stimuli that could support the economic development of a country. In addition, the digitization of monetary transactions around the world is also a major factor requiring the use of e-wallets by the public, thereby increasing the number of users in the future. This research is certainly quite important to do because it is hoped that it can add insight to the public about the LinkAja e-wallet and also help the LinkAja company to find out what things affect people's intentions to use LinkAja as their e-wallet so that the company can adjust its development. going forward with variables that do affect the desire to use LinkAja.